Tobacco Toxicity in Tobacco Chewers (Medico Legal Update, 2020)
Nicotine is highly addictive plant derived alkaloid and the most important species in human use today isNicotiana tabacum. There are direct health effects of chronic nicotine exposure. Even in low doses, nicotinecauses vasoconstriction and other cardiovascular effects related to catecholamine release and promoteangiogenesis, neuroteratogenicity, and possibly some cancers¹. Periodontal disease and dental cavitiesand have up to 48 times the risk of oropharyngeal cancers compared with people who do not use tobaccoproducts². Low doses exposure produces fine tremor, cutaneous vasoconstriction, increased GI motility, andincrease in heart rate, respiratory rate and blood pressure³. Low dose nicotine also increases mental alertnessand produces euphoria and desired psychoactive effects³. Metabolism is via the hepatic cytochrome oxidasesystem. The half life of nicotine in the body is 1 to 4 hours and decreases with repeated nicotine exposure4.